African Women Vulnerability Index: Focus on rural women - Vanessa Tchamyou; Samba Diop; Simplice Asongu; Joseph Nnanna (African Governance and Development Institute (AGDI), 2023)
In this paper, we develop a new index labelled the African Women Vulnerability Index (AWVI) with a focus on rural women using Round 7 of the Afrobarometer Survey. The AWVI comprises 59 indicators in six dimensions namely: safety, empowerment, health, education, economic prosperity and digitalisation. Our findings show that: (i) Botswana performs best while women in Guinea and Sudan are the most vulnerable. Indeed, Mauritius appears as a good example in some dimensions such as health and digitalisation. (ii) Except for the dimension of digitalisation, rural women's vulnerabilities in other dimensions are very close to those at the national level. (iii) National vulnerability trends strongly explain rural women's vulnerability especially for the economic, empowerment and health dimensions.
Keywords: C43; O18; O55; 330; Index creation; gender; rural analysis; Africa